2016
DOI: 10.1002/ajmg.a.37754
|View full text |Cite
|
Sign up to set email alerts
|

A de novo microtriplication at 4q21.21‐q21.22 in a patient with a vascular malignant hemangioma, elongated sigmoid colon, developmental delay, and absence of speech

Abstract: The widespread application of array comparative genomic hybridization (aCGH) has provided new insights into the clinical significance of copy number variations (CNVs) in the human genome. Many microdeletion syndromes have recently been linked to corresponding reciprocal microduplication syndromes related to CNVs in the same chromosomal regions. However, the extent of CNVs may not be restricted to only microduplications but may also include microtriplications or even quadruplications. 4q21 microdeletion syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Nevertheless, a deletion encompassing different genomic loci located at chromosome 4q21 resulted in molecular and clinical definitions of the 4q21 microdeletion syndrome [ 21 - 26 ]. Furthermore, a report on microtriplication at 4q21.21-q21.22 unremarkable in the light of present study due to significant phenotypic and molecular differences, has been recently published [ 27 ]. Original research presenting the first molecular definition of the 4q21 microdeletion syndrome described 9 children with this syndrome with various microdeletions encompassing different regions of the long arm of chromosome 4: 4q21.1q21.22, 4q21.1q21.23, 4q13.3q21.21, 4q21.21q22.3, 4q21.21q21.22, 4q13.3q21.23, 4q21.21q21.23 [ 21 ].…”
Section: Introductionmentioning
confidence: 82%
“…Nevertheless, a deletion encompassing different genomic loci located at chromosome 4q21 resulted in molecular and clinical definitions of the 4q21 microdeletion syndrome [ 21 - 26 ]. Furthermore, a report on microtriplication at 4q21.21-q21.22 unremarkable in the light of present study due to significant phenotypic and molecular differences, has been recently published [ 27 ]. Original research presenting the first molecular definition of the 4q21 microdeletion syndrome described 9 children with this syndrome with various microdeletions encompassing different regions of the long arm of chromosome 4: 4q21.1q21.22, 4q21.1q21.23, 4q13.3q21.21, 4q21.21q22.3, 4q21.21q21.22, 4q13.3q21.23, 4q21.21q21.23 [ 21 ].…”
Section: Introductionmentioning
confidence: 82%
“…Over 1500 children with idiopathic intellectual disability were examined as part of the European Union project “Improving Diagnoses of Mental Retardation in Children in Eastern Europe and Central Asia through Genetic Characterisation and Bioinformatics/Statistics” (CHERISH), and the RIMG identified several novel chromosomal microdeletions and microduplications [4649]. All clinical and molecular protocols were introduced into the Genetics Clinic of the RIMG in Tomsk and are now available to patients.…”
Section: The Modern Landscape Of Psychiatric Genetics In the Russian mentioning
confidence: 99%
“…At present, few studies have focused on the function of ENOPH1. Microdeletion at chromosome 4q21, which contains the ENOPH1 gene, can cause 4q21 microdeletion syndrome, which leads to growth restriction and severe stunting (Bhoj et al, 2013; Bonnet et al, 2010; Iourov, Zelenova, Vorsanova, Voinova, & Yurov, 2018; Komlosi et al, 2015; Lebedev, Nazarenko, Skryabin, Babushkina, & Kashevarova, 2016). Zhang et al (2016) identified ENOPH1 as a new therapeutic target for ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%